The Changing Landscape of Anticoagulation in Pediatric Extracorporeal Membrane Oxygenation: Use of the Direct Thrombin Inhibitors - Neunert, Cindy; Chitlur, Meera; van Ommen, Cornelia Heleen (Frontiers in Medicine, 2022)
Bleeding and thrombosis frequently occur in pediatric patients with extracorporeal membrane oxygenation therapy. Until now, most patients are anticoagulated with unfractionated heparin. However, heparin has many disadvantages, including binding to other plasma proteins and endothelial cells in addition to antithrombin, causing an unpredictable response, challenging monitoring, development of heparin resistance and risk of heparin-induced thrombocytopenia. Direct thrombin inhibitors, such as bivalirudin might be a good alternative. This review will discuss the use of both unfractionated heparin and bivalirudin in pediatric patients with extracorporeal membrane oxygenation therapy.